Childhood Guillain-Barré Syndrome- Comparing Intravenous Immunoglobulin Treatment with Supportive Care: Best Case Study - Award Sponsored by GlaxoSmithKline - McLean, Sarah; Oon, Sheng F. (Trinity Student Medical Journal, 2005)
Objectives: Guillain-Barré Syndrome (GBS) is an acute ascending flaccid paralysis that is often preceded by a mild bacterial or viral infection. Management options include supportive care, physiotherapy, intravenous immunoglobulin (IVIG) and plasmapheresis. Our aim was to compare IVIG treatment and supportive care to supportive care alone in cases of moderate to severe GBS in children less than 16 years of age. Methods: Using specific keywords, the Cochrane Library and PubMed were searched. Eight relevant articles were found and appraised. The studies compared specific outcome criteria including mortality, days taken to regain independent locomotion, days taken to improve by one disability grade on Hughes’ Functional Scale, days of hospitalisation and need for mechanical ventilation. Results: Four articles concluded definite benefits from the use of IVIG in GBS and two articles concluded that there was no difference in outcome with IVIG. One study showed statistically significant benefits with IVIG regarding death and need for mechanical ventilation. No studies showed statistically significant differences regarding recovery times or days of hospitalisation. Conclusion: The articles concurred with the data on GBS in adults, that timely use of IVIG reduces mortality and morbidity in a paediatric setting. However, IVIG use made no difference in the incidence of long-term sequelae of GBS. Sample sizes were small. Larger studies are needed in order to fully explore the benefits of IVIG with regard to these outcome criteria. Logistically and ethically, this would be difficult and no randomised controlled trials have been done to date for this reason. Acute relapse was a new phenomenon, which had not been previously noted in the pre-IVIG era and warrants further investigation.